2022
DOI: 10.3389/fcell.2022.867257
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin C-Cdk8 Kinase Phosphorylation of Rim15 Prevents the Aberrant Activation of Stress Response Genes

Abstract: Cells facing adverse environmental cues respond by inducing signal transduction pathways resulting in transcriptional reprograming. In the budding yeast Saccharomyces cerevisiae, nutrient deprivation stimulates stress response gene (SRG) transcription critical for entry into either quiescence or gametogenesis depending on the cell type. The induction of a subset of SRGs require nuclear translocation of the conserved serine-threonine kinase Rim15. However, Rim15 is also present in unstressed nuclei suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…It was shown that the CKM in several situations acts in opposition to the core Mediator [2,9]. This could be explained by the fact that some components (CDK8/19, MED12) of the Mediator have functions which are independent of the whole complex [9][10][11][12]25,43]. For example, CDK8/19 phosphorylates several targets outside of the transcription machinery, and the Mediator itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the CKM in several situations acts in opposition to the core Mediator [2,9]. This could be explained by the fact that some components (CDK8/19, MED12) of the Mediator have functions which are independent of the whole complex [9][10][11][12]25,43]. For example, CDK8/19 phosphorylates several targets outside of the transcription machinery, and the Mediator itself.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that functions of the Mediator and its CKM are determined by phosphorylation and mechanical interactions lead to the hypothesis that the Mediator can have kinase-dependent and independent functions, and those inhibitors of CDK8/19 would not always phenocopy the knockouts of Mediator components. Although conclusive evidence has not yet been collected, there are data indicating that several members of the mediator complex-MED28 [7] and MED31 [8]-and especially the CKM [9][10][11][12] can perform some functions independent of the Mediator.…”
Section: Introductionmentioning
confidence: 99%